214k views
18 votes
(6x - 3) - (-3x + 2)

User Livibetter
by
5.1k points

1 Answer

5 votes

Answer:

Explanation:

Simplifying

6x + -3 = (3x + -2)

Reorder the terms:

-3 + 6x = (3x + -2)

Reorder the terms:

-3 + 6x = (-2 + 3x)

Remove parenthesis around (-2 + 3x)

-3 + 6x = -2 + 3x

Solving

-3 + 6x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-3 + 6x + -3x = -2 + 3x + -3x

Combine like terms: 6x + -3x = 3x

-3 + 3x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0

-3 + 3x = -2 + 0

-3 + 3x = -2

Add '3' to each side of the equation.

-3 + 3 + 3x = -2 + 3

Combine like terms: -3 + 3 = 0

0 + 3x = -2 + 3

3x = -2 + 3

Combine like terms: -2 + 3 = 1

3x = 1

Divide each side by '3'.

x = 0.3333333333

Simplifying

x = 0.3333333333

User Emil H
by
5.0k points